(untitled) (International Journal of Atharva, 2025)
Self-comparison is a common psychological phenomenon that can significantly impact students’ self-esteem, motivation, and mental health. This study aimed to assess the extent of self-comparison among healthcare students and its relationship with self-esteem, academic performance, and emotional well-being. Additionally, it explored how self-comparison influences students’ perceptions of their abilities in relation to their peers. Using a descriptive research design, the study surveyed healthcare students in an academic setting through a structured questionnaire to measure levels of self-comparison. A quantitative approach was employed to analyze the collected data, with SPSS (Statistical Package for the Social Sciences) utilized for hypothesis testing. The findings indicated that students engaging in upward self-comparison experienced both positive and negative academic and emotional outcomes. The results suggest that the frequency and nature of self-comparison may play a crucial role in students’ overall well-being and mental health, offering insights into their emotional states within a highly competitive academic environment.